2021
DOI: 10.21744/ijhms.v4n4.1779
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructive and restorative interventions at the proximal end of the thigh and pelvic bones in destructive pathological dislocation of the hip in children after hematogenous osteomyelitis

Abstract: It is generally known that children tend to get injured more easily than adults. Moreover, these injuries they get in growing period may leave for long in the forms of disability. This paper is about reconstructive and restorative interventions at the proximal end of the thigh and pelvic bones in destructive pathological dislocation of the hip in children after hematogenous osteomyelitis. After hematogenous osteomyelitis of the proximal end of the femur, destruction of the head and neck of the femur is often o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The subjective parameter showed that the children were able to identify their pain intensity and sites of pain. 9 As per the above studies and evidence the researcher felt that sponge ball may have a beneficial effect on the reduction of pain and the perception of the pain of the hospitalized child. Squeezing a sponge ball during insertion of the intravenous cannula can be an affordable, easily assessable, lowcost, and effective method to reduce pain among children.…”
Section: Need Of the Studymentioning
confidence: 84%
“…The subjective parameter showed that the children were able to identify their pain intensity and sites of pain. 9 As per the above studies and evidence the researcher felt that sponge ball may have a beneficial effect on the reduction of pain and the perception of the pain of the hospitalized child. Squeezing a sponge ball during insertion of the intravenous cannula can be an affordable, easily assessable, lowcost, and effective method to reduce pain among children.…”
Section: Need Of the Studymentioning
confidence: 84%
“…Due to the patient's inability to wear spectacles, contact lenses were scheduled to be fitted . High astigmatism, keratoconus severity, topography analysis, occupation, allergy history, ocular surface or dry eye history, and cost were used to determine lens type (Alpysbaev et al, 2021). The most popular and successful option for keratoconus is a rigid gas permeable (RGP) lens on the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…Some research tested the effectiveness of low-level laser (LLLT 905 nm) or Fascial distortion Model (FDM) in treating groin adductor strain separately, but, up to our knowledge, no controlled randomized research directly compared the efficacy of both modalities. Therefore, the present study aimed to investigate the efficacy of PBM (905 nm) and FDM on CKmm, LDH5, and pain level on groin adductor strain in handball athletes (Alpysbaev et al, 2021).…”
Section: Introductionmentioning
confidence: 99%